Prevalence of and Risk Factors for Caregiver Burden in Palliative Care in Thailand - Chumintrachark, Alicha; Buawangpong, Nida; Ratanasaard, Chanaphon; Pinyopornpanish, Kanokporn; Dejkriengkraikul, Nisachol; Chutarattanakul, Lalita; Ratanasiri , Thawalrat (Biomedical Sciences and Clinical Medicine, 2024)
Objective Caregivers are highly important in both conventional and palliative care. Their responsibilities, which include biological, psychological, and social aspects, can lead to stress and other complications. The objectives of this study were to determine (i) the prevalence of caregiver burden in palliative care and its severity, and (ii) risk factors associated with caregiver burden in palliative care settings. Methods This cross-sectional study was conducted with palliative care patients and main caregivers in palliative care in both in- and out-patient departments of a hospital in Thailand. Baseline characteristics of caregivers and patients, including patients’ quality of life, caregivers’ self-efficacy, and caregiver burden were collected using Zarit Burden Interview (ZBI) scores. Linear regression was used to determine the association between caregiver burden and potential risk factors. Results One hundred and two caregivers and their patients were included in the analysis. Caregivers’ mean age was 48.2±13.1 years. Most were female (77.5%) and married (65.7%). The mean age of the 102 patients of those caregivers was 64.9±13.8 years. The majority were female (57.8%) and most lived together with their caregiver (72.6%). The mean ZBI score of the caregivers was 13.4±13.9 of whom one-fourth had experienced caregiver’s burden (23.53%), with most having mild severity (17.7%). Factors negatively associated with ZBI scores were the patient’s quality of life (coefficient -0.46, 95% CI -0.89 to -0.04, p = 0.027) and the caregiver’s self-efficacy (coefficient -0.17, 95% CI -0.31 to -0.02, p = 0.033). Conclusions The prevalence of caregiver burden in Thai palliative caregivers is relatively small. Greater caregiver self-efficacy and improved patient quality of life may help reduce caregiver burden. Assessment of caregiver burden level should be included as an integral aspect of the patient-care process.